Real time implementation of anti-windup PI controller for speed control of induction machine based on DTC strategy - Lahcen Ouboubker; Jawad Lamterkati; Mohamed Khafallah; Aziz El Afia (Institute of Advanced Engineering and Science, 2021)
This paper presents simulation and experimental results of anti-windup PI controller to improve induction machine speed control based on direct torque control (DTC) strategy. Problems like rollover can arise in conventional PI controller due to saturation effect. In order to avoid such problems anti-windup PI controller is presented. This controller is simple for implementation in practice. The proposed anti-windup PI controller demonstrates better dynamic step changes response in speed in terms of overshoots. All simulation work was done using Simulink in the MATLAB software. The experimental results were obtained by practical implementation on a dSPACE 1104 board for a 1.5 KW induction machine. Simulation and experimental results have proven a good performance and verified the validity of the presented control strategy.